A Flexible Robotic Arm with Hydraulic Skeleton - Hitoshi KIMURA; Mokutaro KATAOKA; Shotaro SUZUKI; Daisuke AKIMOTO; Norio INOU (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2012)
This study aims to build a totally flexible mechanical system with hydraulic skeleton driving mechanism. The main components of this system are two types of flexible bags. One is a structural bag with constant inner pressure. The other is an actuator bag with controlled inner pressure. Such flexible system will provide various advantages, for example, safety, portability, lightweight and dealing with fragile objects. Efficiency is also an advantage because only actuator parts consume driving fluid with the proposed system. This paper deals with a flexible robotic arm as an example of the proposed mechanism. With geometric relationship, effective parts arrangement and driving force at the joint are discussed in this paper. Quantitative estimations of structural deformation and driving force of flexible bags are important for design of the proposed system. However, numerical analysis of flexible bags is difficult because of their large nonlinear deformation. This study tries to analyze large nonlinear deformations of flexible bags with the nonlinear finite element analysis software ABAQUS. From the analytical results, this paper discusses unique effects of structural deformation depending on the driving force. The validity of the analysis is verified by experimental results. Both results show that the effect of concave deformation of a structural bag at the joint is 10 times larger than normal cantilever deformation. Pick and place motion of a raw egg is also performed with a proposed robotic arm avoiding large concave deformation without complex control such as force sensing and so on.